Pengaruh Pengetahuan Kewirausahaan dan Media Sosial terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha - Giri, Evi Lila Sari; Sujana, I Nyoman (Universitas Pendidikan Ganesha, 2023)
In carrying out this research activity, the objectives were to test: (1) the influence exerted by entrepreneurial knowledge on student entrepreneurial interest, (2) the influence exerted by social media on student entrepreneurial interest, and (3) the influence exerted by entrepreneurial knowledge and social media on student entrepreneurship interest. This type of research uses causalitative research. The population used was in the form of students from the Faculty of Economics who had succeeded in obtaining existing entrepreneurship courses in the 2019 to 2022 school year with a total of 1,842 people, so that the sample was ultimately used with a total of 329. The sample technique that the researchers used was a simple random sampling technique. The method used in carrying out the process of data collection activities is in the form of a questionnaire using multiple linear regression analysis. In the final stage of testing the hypothesis in the form of a t test and F test which are processed with the help of an application called SPSS 25 for windows. The results of research activities show that: (1) entrepreneurship knowledge has an influence that leads to positive results and also significant results on student entrepreneurship interest, (2) social media has an influence that leads to positive results and also significant results on student entrepreneurship interest, and (3) entrepreneurial knowledge and social media have an influence that leads to positive results and also significant results on student interest in entrepreneurship.